Principles of medullary thyroid cancer staging according to AJCC TNM 8th edition - O.R Duda (Danylo Halytsky Lviv National Medical University, 2021)
Aim. The research aims at analyzing the main changes in classification of medullary thyroid cancer and outlining the principles of staging according to modern studies.